Palimpsestuous IntertextualitiesAdaptations for Young Audiences: Critical Challenges, Future Directions. Issue 2 (December 2016) - McCallum, Robyn
Abstract : Historically, literary sources have always provided a rich resource for film narratives, meaning that the history of cinema is closely intertwined with the history of film adaptation. Children's literature in particular has been a favoured source of represented narratives. Some of the earliest film adaptations were of children's texts, many of which have been readapted multiple times. Adaptation studies has been a growth area of scholarly research and debate for at least five decades. However, despite the close imbrication of the film industry and children's literature since the early twentieth century, few adaptation scholars have turned their attention to the rich resource that children's and youth culture provides. This paper surveys dominant shifts in approaches to adaptation, in particular the shift from 'fidelity criticism' to a dialogic intertextual approach; the recent move back to a modified form of 'fidelity criticism'; and the cultural work that has thus far been achieved in the field of adaptation studies and children's and youth culture. In doing so it examines the critical challenges faced by scholars in the field and the potent possibilities future scholarship might pursue.